Un terrain miné, un travail de déminage ou comment parler de l’oppression des femmes minorisées en tant que chercheuse de la majorité - Iavarone-Turcotte, Anne (2023)
Dans cet article, je présente la manière dont j’ai abordé, pour tenter de les atténuer, les risques découlant de ma prise de parole sur mon objet d’étude doctorale : l’oppression des femmes dans les minorités religieuses. Ces risques découlant de mon positionnement de féministe blanche occidentale, membre de la majorité libérale et laïque, et détentrice de nombreux privilèges associés à ces statuts, j’ai résolu de modifier symboliquement ce positionnement dans ma recherche. Pour ce faire, j’ai élaboré et appliqué une méthodologie réflexive dont l’un des aspects clés, présenté dans l’article, a été de (re)tourner mon regard critique vers moi.
Keywords: 2000 à aujourd'hui; 2020-2029; amérique du nord; amériques; approches et analyses; cours; discipline; inégalités; justice sociale; phi4336; philosophie; point de vue situé; premier cycle; privilèges; pédagogie; périodes historiques; québec; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques

Justice and the politics of difference - Young, Iris Marion; Allen, Danielle S. (Princeton University Press, 2022)
"In this classic work of feminist political thought, Iris Marion Young challenges the prevailing reduction of social justice to distributive justice. The starting point for her critique is the experience and concerns of the new social movements that were created by marginal and excluded groups, including women, African Americans, and American Indians, as well as gays and lesbians. Young argues that by assuming a homogeneous public, democratic theorists fail to consider institutional arrangements for including people not culturally identified with white European male norms. Consequently, theorists do not adequately address the problems of an inclusive participatory framework. Basing her vision of the good society on the culturally plural networks of contemporary urban life, Young makes the case that normative theory and public policy should undermine group-based oppression by affirming rather than suppressing social group differences"
Section: x, 286 pages ; 24 cm.
Keywords: 2000 à aujourd'hui; 2010-2019; amérique du nord; amériques; approches et analyses; cours; cycles supérieurs; discipline; discours dominant; fem9000; inégalités; justice sociale; phi4336; philosophie; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; états-unis

Metaepistemic Injustice and Intellectual Disability: a Pluralist Account of Epistemic Agency - Catala, Amandine (Ethical Theory and Moral Practice, 2020)
The literature on epistemic injustice currently displays a logocentric or propositional bias that excludes people with intellectual disabilities from the scope of epistemic agency and the demands of epistemic justice. This paper develops an account of epistemic agency and injustice that is inclusive of both people with and people without intellectual disabilities. I begin by specifying the hitherto undertheorized notion of epistemic agency. I develop a broader, pluralist account of epistemic agency, which relies on a conception of knowledge that accounts not only for propositional knowing, but also for other types of knowing that have been largely neglected in debates on epistemic injustice and agency. Based on this pluralist account of epistemic agency, I then show that people with intellectual disabilities qualify as epistemic agents and therefore as subjects of epistemic justice. Finally, I argue that this pluralist account of epistemic agency pushes us to revisit the current conception of epistemic injustice and to expand its taxonomy in two important ways.
Keywords: EDI; agentivité épistémique; approches et analyses; capacitisme; cours; cycles supérieurs; discipline; fem9000; handicap intellectuel; injustices épistémiques; inégalités; justice sociale; justice épistémique; philosophie; savoir propositionnel; sciences humaines; systèmes d'oppressions; taxonomie des savoirs; thématiques; violences; éthique

Microaggressions and philosophy - Freeman, Lauren; Weekes Schroer, Jeanine (Routledge, 2020)
"This is one of the first books to offer a comprehensive philosophical treatment of microaggressions. Its aims are to provide an intersectional analysis of microaggressions that cuts across multiple groups and dimensions of oppression and marginalization, and to engage a variety of perspectives that have been sidelined within the discipline of philosophy. The volume gathers a diverse group of contributors: philosophers of color, philosophers with disabilities, philosophers of various nationalities and ethnicities, and philosophers of several genders and gender identities. Their unique frames of analysis articulate both how the concept of microaggressions can be used to clarify and sharpen our understanding of subtler aspects of oppression and how analysis, expansion, and reconceiving the notion of a microaggression can deepen and extend its explanatory power. The essays in the volume are divided into four thematic parts. The essays in Part I seek to defend microaggressions from common critiques and to explain their impact beyond the context of college students. In Part II the contributors set forth a framework for legitimizing microaggressions research that takes into account issues of measurement, scale, and replication. Part III explores the harms of microaggressions. The chapters show how small slights can accumulate to produce significant harm at the macro level, demonstrate how microaggressions contribute to epistemic harm, and establish novel understandings of racial and accent-triggered microaggressions. Finally, Part IV addresses issues of disability and ableism within the context of microaggressions. It includes commentary on transgender athletes, disciplinary techniques for bodily nonconformity, ableist exceptionalism, and deafness. Microaggressions and Philosophy features cutting-edge research on an important topic that will appeal to a wide range of students and scholars across disciplines. It includes perspectives from philosophy of psychology, empirically informed philosophy, feminist philosophy, critical race theory, disability theory, philosophy of language, philosophy of science, and social and political philosophy"– Provided by publisher.
Keywords: EDI; approches et analyses; capacitisme; cours; cycles supérieurs; discipline; fem9000; histoire et politique; hétérosexisme; intersectionnalité; inégalités; micro-agression; philosophie; psychologie; racisme; sciences humaines; sexisme; sofia; systèmes d'oppressions; thématiques; transphobie; violences; études critiques de la race; études critiques du handicap